Kebijakan Pemerintah dalam Pengelolaan Sumber Daya Alam: Studi Kasus Indonesia - Purba, Bonaraja; Situmorang, Eva Juli Yanti; Annurradi, M.Abdan Syakura; Siagian, Hernita; Hutagalung, Marsanda (Economic Reviews Journal, 2024)
This study shows that government policies face major challenges in managing natural resources in Indonesia, especially in the fields of fisheries, plantations and mining. Government policies in managing natural resources must be implemented optimally, fairly, sustainably and environmentally friendly. In the fisheries sector, government policies must pay attention to the principles of sustainability, setting fishing quotas and protecting marine protected areas. However, implementation often faces complex regulatory challenges and resistance from industry stakeholders. In the plantation sector, government policies must ensure that plantation business activities can run optimally and provide benefits to the surrounding community. The administrative sanctions imposed must be more effective than just fines. In the mining sector, government policies must consider land rights and mining rights. Mineral rights do not eliminate rights to the land above them and must be regulated based on an agreement between the parties involved. Possible solutions to increase the efficiency and effectiveness of policy implementation include improving coordination between government institutions and increasing institutional capacity. Community participation in decision making is also an important element in sustainable natural resource management.